Modularity and the Impact of Buyer–Supplier Relationships on the Survival of Suppliers - Hoetker, Glenn; Swaminathan, Anand; Mitchell, Will (Management Science, 2007)
Modularity in product design and flexible supply chains is increasingly common in buyer–supplier relationships. Although the benefits of supply chain flexibility and component modularity for end-product manufacturers are accepted, little is known about their impact on suppliers. We advance the literature on modularity by exploring how three aspects of a supplier’s relationships with its customers affect the supplier’s survival: duration of buyer–supplier relationships, autonomy from customers, and links to prominent buyers. We compared the effects of these aspects of buyer–supplier relationships for low- and high-modularity components. Using data on U.S. carburetor and clutch manufacturers from 1918 to 1942, we found that suppliers of high-modularity components benefited more from autonomy provided by potential customers, whereas suppliers of low-modularity components benefited more from ties to higher status customers. Both benefited from autonomy generated by existing customers. Thus, relationships that require trust and extensive sets of interfirm routines, as do those for low-modularity components, led to both greater relationship benefits and greater constraints.